Zastosowanie metody SWOT w diagnozie uwarunkowań rozwoju partnerstwa w Dolinie Lotniczej - Moszkowicz, Krystyna; Bembenek, Bogusław (The Use of SWOT Method in Diagnosis of Conditions for Development Partnership in Aviation Valley, 2008)
Based on theoretical and empirical studies the authors of this article concentrate on the diagnosis of conditioning of partnership development in Aviation Valley. The article presents chances, threats, strengths and weaknesses which are important from the point of view of partnership development in Aviation Valley.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 246-255